Amicable settlement of conflicts between agri-food producers and consumers - Ioan Niculae Alecu; Felix-Dimitrie Ciocan; Gabriela Gyongy Mihuţ (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Similarly to how not knowing the laws and obligations resting upon a person will not exempt that person from liability, consumers not knowing their rights and not using them might place them into a position of inferiority when it comes to the relationships with the producers or distributors of agri-food products. Although, theoretically, such relationships mean that the parties are equal from a legal point of view, having correlative rights and obligations, in fact, given the nature of the products making up the object of the relationship between the producer and consumer, the consumer is place a priori in a position where he has to award maximum diligence, since we are talking about actions that might have consequences upon his health and even life. Returning to the previous state, fixing contingent damages and regaining the mutual respect and trust inherent to a healthy commercial demeanor, in case of conflict, determines the studying of alternative settlement procedures for conflicts, a stand out being the procedure of mediation, a procedure that is an alternative to the court of law. The institution of mediation can be understood through an exhaustive presentation of the framework law in the field, of the related laws, these being different from the European law in the field, the latter being included ope legis into the national framework law, through the ratification process or through undertaking the community acquis.
Keywords: 330; mediation; consumer; agri-food; producer; conflict